Initiatives to improve adolescent knowledge about premarital in stunting prevention in Donorojo, Magelang - Tantri Harwati; Brune Indah Yulitasari; Anggi Widiyanti; Anggita Fatimah Nurbaiti; Eka Septi Seliani Mutia; Rizka Utami; Isti Hanifah; Sintya Dewi Indrawati; Naufal Adam Hibatullah; Muhammad Faisal Basri; Choiri Mahmud (Universitas Muhammadiyah Magelang, 2023)
Stunting is a nutritional problem in the world, especially in poor and developing countries. Stunting is a problem that leads to delays in motor development and mental growth. This counseling activity aims to increase adolescent knowledge about premarital to prevent stunting in Donorojo Tegalrejo Village, Magelang Regency. The counseling activity was attended by 40 youths from Donorojo Village. This activity was carried out with pre-test, counseling on premarital preparation, and post-test. Counseling activities succeeded in increasing adolescent premarital knowledge in preventing stunting by 5.41%.